Are recent graduates enough prepared to perform obstetric skills in their rural and compulsory year? A study from Ecuador. Issue 7 (31st July 2014) - Sánchez del Hierro, Galo; Remmen, Roy; Verhoeven, Veronique; Van Royen, Paul; Hendrickx, Kristin
Abstract : Objectives: The aim of this study was to assess the possible mismatch of obstetrical skills between the training offered in Ecuadorian medical schools and the tasks required for compulsory rural service. Setting: Primary care, rural health centres in Southern Ecuador. Participants: A total of 92 recent graduated medical doctors during their compulsory rural year. Primary and secondary outcomes measures: A web-based survey was developed with 21 obstetrical skills. The questionnaire was sent to all rural doctors who work in Loja province, Southern Ecuador, at the Ministry of Health (n=92). We measured two categories: 'importance of skills in rural practice' with a five-point Likert-type scale (1= strongly disagree; 5= strongly agree); and 'clerkship experience' using a nominal scale divided in five levels: level 1 (not seen, not performed) to level 5 (performed 10 times or more). Spearman's rank correlation coefficient (r) was used to observe associations. Results: A negative correlation was found in the skills: 'episiotomy and repair', 'umbilical vein catheterisation', 'speculum examination', 'evaluation of cervical dilation during active labour', 'neonatal resuscitation' and 'vacuum-assisted vaginal delivery'. For instance 'Episiotomy and repair' is important (strongly agree and agree) to 100% of respondents, but in practice, only 38.9% of rural doctors performed the task three times and 8.3% only once during the internship, similar pattern is seen in the others. Conclusions: In this study we have noted the gap between the medical needs of populations in rural areas and training provided during the clerkship experiences of physicians during their rural service year. It is imperative to ensure that rural doctors are appropriately trained and skilled in the performance of routine obstetrical duties. This will help to decrease perinatal morbidity and mortality in rural Ecuador.